Modelling graduate unemployment from students' perspectives / Noor Ilanie Nordin …[et al.] - Nordin, Noor Ilanie; Mohamad Sobri, Norafefah; Ismail, Nor Azima; Mahmud, Maziah; Alias, Nurain Alia; Hashim, Siti Nurini; Murad, Muhammad Aiman Hafizi (2022)
The purpose of this study is to examine the significant difference in mean on graduate unemployment from students' perspectives between genders and to study the factors that influence graduate unemployment from students' perspectives and also their relationship. This study is aimed at undergraduate students of UiTM Kota Bharu Campus in Kelantan, as the population. Two hundred and ninety-three students were selected as the respondents using the stratified sampling technique. A cross-sectional design was used to collect primary data, and SPSS was used to analyze the primary data that had been collected. The study indicated a significant difference in mean on graduate unemployment from students' perspectives between genders on Independent T-test analysis. The independent variables had a moderate positive correlation with the dependent variable using Pearson Correlation. Furthermore, from the Multiple Linear Regression analysis conducted, three independent variables, unrealistic salary, academic performance, and graduate attributes, significantly affect graduate unemployment from students’ perspectives. However, employability skills do not significantly affect graduate unemployment from students' perspectives. Therefore, this study can help future graduates to prepare themselves before venturing into the realm of work.